A middleware architecture for mobile 3D graphics - AGU, EMMANUEL; BANERJEE, KUTTY; NILEKAR, SHIRISH; REKUTIN, OLEG; KRAMER, DIANE (International journal of parallel, emergent and distributed systems, 2006)
Mobile graphics, which involves running networked computer graphics applications on mobile devices across wireless networks, is a fast growing segment of the networks and graphics industries. Running networked graphics applications in mobile environments faces a fundamental conflict; graphics applications require large amounts of memory, CPU cycles, battery power and disk space, while mobile devices and wireless channels tend to be limited in these resources. In order to mitigate mobile environment issues, some form of adaptation based on a client device's capabilities, prevailing wireless network conditions, characteristics of the graphics application and user preference, is necessary. In this paper, we describe the mobile adaptive distributed graphics framework (MADGRAF), a graphics-aware middleware architecture that makes it feasible to run complex 3D graphics applications on low-end mobile devices over wireless networks. In MADGRAF, a server can perform mobile device-optimized pre-processing of complex graphics scenes in order to speed up run time rendering, scale high-resolution meshes using polygon or image-based simplification, progressively transmit compressed graphics files, conceal transmission errors by including redundant bits or perform remote execution, all tailored to the client's capabilities. MADGRAF exposes our mobile adaptive distributed graphics language (MADGL), an API that facilitates the programming and management of networked 3D graphics in mobile environments.